Knowledge, attitudes and practices of slaughters on hydatidosis/echinococcosis in two Ica Department, Peru urban areas - Cabrera, Rufino (2005)
Objectives: To determine the knowledge, attitudes and practices of slaughter workers from Ica and Chincha, Ica, Peru on Echinococcus granulosus and hydatidosis/ echinococcosis. Materials and Methods: Observational, descriptive study on fifty-five workers interviewed anonymously on E. granulosus and hydatidosis/ echinococcosis in December 2000. Results: The E. granulosus metacestode was called ‘water bag’ by 25 (45,5%) of the workers and hydatid cysts by 10 (18,2%). The cattle and sheep were mostly identified as intermediate hosts but the workers would not know the definitive hosts or transmission mechanisms. Thirty six (65,5%) slaughters considered they would receive treatment if infected and 17 (30,9%) would eliminate their dogs if they would observe helminthes in their feces stools. A group of 21 workers (38,2%) admitted that hydatid cysts are left on the abattoir floor, 30 (54,5%) raised dogs and 19 (63,3%) had not given treatment for parasites to their pets in the past six months. Thirty (54,5%) workers made clandestine cattle slaughtering and some fed their dogs with parasitized crude viscera. Conclusions: The interviewed slaughters knowledge on hydatidosis/echinococcosis was deficient and their practices favored hydatidosis transmission and spread.